AN ANALYSIS OF ULI STELZNER’S “LA ISLA” (2009) AND HERNÁN JIMÉNEZ’S “A OJOS CERRADOS” (2010) - Poe, Karen (2013)
This essay analyzes mourning from a psychoanalytic perspective in two Central American films. Documentary “La isla, archivos de una tragedia” by German director Uli Stelzner introduces mourning on disappeared people (“desaparecidos”) in Guatemala after genocide. “A ojos cerrados” by Costa Rican director Hernán Jiménez, presents mourning issues at a middle class family in San José downtown, Costa Rica.